Transanal evisceration of small bowel in two patients with chronic rectal prolapse: case presentation and literature review - Hajiev, S (Ann R Coll Surg Engl, 2021)
There are fewer than 100 documented cases of transanal small bowel evisceration in the literature. We report two cases of this rare surgical emergency in an 84-year old man and a 79-year old woman. Both patients required urgent laparotomy, resection of ischaemic bowel and transabdominal resection of the rectal defect with colostomy. Postoperative recovery was uneventful. Rare imaging and clinical photography are shared to highlight the extreme nature of this condition. We identified 38 relevant cases of reported bowel evisceration through our literature review. Most patients were elderly women with untreated rectal prolapse. Gynaecological comorbidity was another risk factor. The aetiological mechanism is suspected to stem from chronic ischaemic insult to the rectal wall, resulting in thinning and subsequent perforation. Surgical management may consist of primary suture repair of the rectal tear, or a Hartmann’s procedure. Timely intervention is essential to minimise patient morbidity and mortality.